Comparison of simulated and observed horizontal inhomogeneities of optical thickness of Arctic stratus - Schäfer, Michael; Loewe, Katharina; Ehrlich, André; Hoose, Corinna; Wendisch, Manfred (Universität Leipzig, 2019)
Two-dimensional horizontal fields of cloud optical thickness derived from airborne measurements of solar spectral, reflected radiance are compared with semiidealized large eddy simulations (LESs) of Arctic stratus performed with the Consortium for Small-scale Modeling (COSMO) atmospheric model. The measurements were collected during the Vertical Distribution of Ice in Arctic Clouds (VERDI) campaign carried out in Inuvik, Canada, in April/May 2012. The input for the LESs is obtained from collocated dropsonde observations of a persistent Arctic stratus above the sea-icefree Beaufort Sea. Simulations are performed for spatial resolutions of 50 m (1.6 km by 1.6 km domain) and 100 m (6.4 km by 6.4 kmdomain). Macrophysical cloud properties, such as cloud top altitude and vertical extent, are well captured by the COSMO simulations. However, COSMO produces rather homogeneous clouds compared to the measurements, in particular for the simulations with coarser spatial resolution. For both spatial resolutions, the directional structure of the cloud inhomogeneity is well represented by the model. This study was first published by Schäfer et al., 2018. Zweidimensionale horizontale Felder optischer Dicken abgeleitet aus flugzeuggetragenen Messungen der spektralen, solaren, reflektierten Strahldichte über Arktischem Stratus werden mit teilidealisierten Large Eddy Simulationen (LES) im Atmosphärenmodel des Consortium for Small-scale Modeling (COSMO) verglichen. Die Messungen stammen von der Vertical Distribution of Ice in Arctic Clouds (VERDI) Kampagne in Inuvik, Kanada, im April/Mai 2012. Fallsonden- Beobachtungen eines beständigen arktischen Stratus über dem eisfreien Beaufort Meer bilden die LES-Eingangsdaten. Die Simulationen wurden mit räumlichen Auflösungen von 50 m (1.6 km  1.6 km Gebiet) und 100 m (6.4 km  6.4 km Gebiet) durchgeführt. Makroskopische Wolkeneigenschaften (Wolkenhöhe, -ausdehnung) wurden von COSMO erfasst. Allerdings produziert COSMO verglichen zu den Beobachtungen (besonders bei grober räumlicher ...